The Influence of Age, Adequate Antenatal Care, Education Level, and the Use of Health Information from Social Media on First-time Adolescent Mothers’ Postpartum Behavior - Kitbumrung, Chonthicha; Phahuwatanakorn, Wanna; Pungbangkadee, Rudee (Journal of The Royal Thai Army Nurses, 2024)
This predictive research was to study the influence of age, adequate antenatal care, education level, and the use of health information from social media on first-time adolescent mothers’ postpartum behavior. The sample consisted of 154 first-time teenage mothers, aged 10-19 years, who gave birth and recuperated in the postpartum ward at a tertiary hospital. The research instrument was a questionnaire to collect data. The data were analyzed using descriptive statistics, Point biserial correlation coefficient statistics, Chi-square test and binary logistic regression analysis. The results of the study found that age factor, education level, adequate antenatal care and use of health information from social media together they were able to predict the postpartum behavior of first-time teenage mothers by 13.2% (R2 = .132) with statistical significance (p<.05). It was found that the age factor Education level and using health information from social media can predict postpartum behavior. After the birth of first-time adolescent mothers, there was statistical significance (β = -.462, p<.002, β = 1.138, p<.014 and β = .643, p<.009, respectively). Therefore, if the first-time adolescent mothers have a higher age, educational level, and use more health information from social media, it can be predicted that the postpartum behaviors of these first-time pregnant mothers will increase.